Importance of RS-GIS in Mapping for Sustainable Management of Mangroves with Special Reference to Sunderbans, India - Datta, Debajit; Chattopadhyay, R. N. (National Geographical Journal of India, 2022)
Mangrove forests are in a vulnerable state worldwide due to quasi-natural environmental degradation. Managing mangrove forests in a sustainable ecological as well as economical way is a difficult proposition and needs multi-disciplinary approach. This paper aims to highlight the importance of integration of GIS and remote sensing technologies along with field methods in the management and conservation strategies of the mangrove forests worldwide. Selection of sensors depending on the scale and nature of management activity has been given priority. Special emphasis has been given to the recent studies conducted in Indian subcontinent in general and on the Sunderbans in particular.